Anti‐viral therapy is associated with improved survival but is underutilised in patients with hepatitis B virus‐related hepatocellular carcinoma: real‐world east and west experience. Issue 1 (24th May 2018) - Chen, V. L.; Yeh, M.‐L.; Le, A. K.; Jun, M.; Saeed, W. K.; Yang, J. D.; Huang, C.‐F.; Lee, H. Y.; Tsai, P.‐C.; Lee, M.‐H.; Giama, N.; Kim, N. G.; et al.
Summary: Background: Hepatitis B virus (HBV) is the leading cause of hepatocellular carcinoma (HCC) worldwide. It remains incompletely understood in the real world how anti‐viral therapy affects survival after HCC diagnosis. Methods: This was an international multicentre cohort study of 2518 HBV‐related HCC cases diagnosed between 2000 and 2015. Cox proportional hazards models were utilised to estimate hazard ratios (HR) with 95% (CI) for anti‐viral therapy and cirrhosis on patients' risk of death. Results: Approximately, 48% of patients received anti‐viral therapy at any time, but only 17% were on therapy at HCC diagnosis (38% at US centres, 11% at Asian centres). Anti‐viral therapy would have been indicated for >60% of the patients not on anti‐viral therapy based on American criteria. Patients with cirrhosis had lower 5‐year survival (34% vs 46%; P  <   0.001) while patients receiving anti‐viral therapy had increased 5‐year survival compared to untreated patients (42% vs 25% with cirrhosis and 58% vs 36% without cirrhosis; P  <   0.001 for both). Similar findings were seen for other patient subgroups by cancer stages and cancer treatment types. Anti‐viral therapy was associated with a decrease in risk of death, whether started before or after HCC diagnosis (adjusted HR 0.62 and 0.79, respectively; P  <   0.001). Conclusions: Anti‐viral therapy improved overall survival in patients with HBV‐related HCC across cancer stages and treatment types but was underutilised at both US and Asia centres. Expanded use of anti‐viral therapy in HBV‐related HCC and better linkage‐to‐care for HBV patients are needed.